2009
DOI: 10.1007/978-3-642-01181-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Creation of Taxonomies of Genetic Programming Systems

Abstract: Abstract. A few attempts to create taxonomies in evolutionary computation have been made. These either group algorithms or group problems on the basis of their similarities. Similarity is typically evaluated by manually analysing algorithms/problems to identify key characteristics that are then used as a basis to form the groups of a taxonomy. This task is not only very tedious but it is also rather subjective. As a consequence the resulting taxonomies lack universality and are sometimes even questionable. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…That is, they cannot easily be used to estimate, for example, the success rate of a GP system or the expected number of fitness evaluations required to solve a problem. Recent work [86,87] has begun to rectify this situation. The work has found that a simple semilinear model can accurately predict the performance of program-induction algorithms for the domains of symbolic regression and Boolean function induction.…”
Section: Problem Difficulty and Performance Models In Gpmentioning
confidence: 93%
See 2 more Smart Citations
“…That is, they cannot easily be used to estimate, for example, the success rate of a GP system or the expected number of fitness evaluations required to solve a problem. Recent work [86,87] has begun to rectify this situation. The work has found that a simple semilinear model can accurately predict the performance of program-induction algorithms for the domains of symbolic regression and Boolean function induction.…”
Section: Problem Difficulty and Performance Models In Gpmentioning
confidence: 93%
“…2.5, the simple performance modelling techniques for GP proposed in [86,87] offer an alternative way of assessing performance, and, hence, difficulty for GP. While these models are simple and approximate, they have provided accurate predictions.…”
Section: Problem Difficulty and Performance Predictionmentioning
confidence: 99%
See 1 more Smart Citation